Analisis Kelembagaan Implementasi Perhutanan Sosial di Provinsi Sumatera Utara - Oding Affandi (Inovasi, 2019)
The Social Forestry (SF) Programme, as one of the policy innovations in forest management in Indonesia, was made so the community has legal rights and access to use the forest. Since the SF programme was issued in 2016, its implementation was still slow and has not supported the achievement of good forest governance. The research objective was to analyze the institutional of the SF implementation. Data collection methods were carried out by interviews, FGD, and document review. The study analysis was carried out descriptively and institutional through a framework approach: Institutions Structure - Characteristic of Resource – Actor Behavior – Performance. The institutional situation of the PS program shown: (1) The North Sumatra Provincial Government did not yet have a specific regulation regarding Facilitation of SF Programme Implementation; (2) The SF programme was able to change the characteristics of forest resource from common pool goods to private goods; (3) differences in actor's interests and power make actor behavior not fully support the SF programme; (4) The performance of the SF programme implementation was categorized as low. To improve institutional performance should be recommended: At the national level, the government issues Presidential Instruction or Presidential Decree and at the provincial level, the regional government issues a Governor's Regulation on Facilitation of SF Implementation; Increasing the capacity and mentoring of SF programme implementing actors; The expert group developed an action plan for enhancing SF programme implementation; To increase the motivation of SF actors, the government organized a Social Forestry Innovation Award; and There were integration of SF programme with forest resource based industries or services and using digital information technology. Keywords: Social Forestry; Institutional; Forest Governance, North Sumatera Province